Implementation of Multi-Stage Converter and Ultra-Capacitor DC Link-Based Voltage Source Active Power Filter - Aung, Lwin Mar (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
A new topology for active power filters (APF) using an 27-level converter is analyzed. Each phase of the converter is composed of three three-state converters, all of them connected to the same capacitor dc link voltage and their output connected in series through output transformers. The power quality is improved by using active power filter. The different power quality problems in distribution systems and their solutions with power electronics based equipment. This power quality problem exists if any voltage, current or frequency deviation results in a failure or in a bad operation of customer’s equipment. A multi-stage inverter using three-state converter is being analyzed for active filter and static var compensator applications. A 1F Ultracapacitor is used in the DC link, making it possible to obtain a very stable voltage at the DC bus, even with highly contaminated currents. This high capacity also makes it possible to continue feeding the contaminating load during a Voltage Dip. Simulation results for this application are based on PIC16F877A assembly language.Active Power Filter